Abstracts from the 15th International Myopia Conference. Issue 1 (November 2016) - Benavente-Perez, Alexandra; Nour, Ann; Ansel, Tobin; Abarr, Kathleen; Yan, Luying; Roden, Keisha; Troilo, David; Lu, Chanyi; Pan, Miaozhen; Zheng, Min; Qu, Jia; Zhou, Xiangtian; et al.
Table of contents O1 Changes in peripheral refraction associated with decreased ocular axial growth rate in marmosets Alexandra Benavente-Perez, Ann Nour, Tobin Ansel, Kathleen Abarr, Luying Yan, Keisha Roden, David Troilo O2 PPARα activation suppresses myopia development by increasing scleral collagen synthesis--a new drug target to suppress myopia development Chanyi Lu, Miaozhen Pan, Min Zheng, Jia Qu, Xiangtian Zhou O3 Evidence and possibilities for local ocular growth regulating signal pathways Christine F Wildsoet O4 Myopia researches at Eye Hospital of Wenzhou Medical University Fan Lu, Xiangtian Zhou, Jie Chen, Jinhua Bao, Liang Hu, Qinmei Wang, Zibing Jin, Jia Qu O5 Color, temporal contrast and myopia Frances Rucker, Stephanie Britton, Stephan Hanowsky, Molly Spatcher O6 The impact of atropine usage on visual function and reading performance in myopic school children in Taiwan Hui-Ying Kuo, Ching-Hsiu Ke, I-Hsin Kuo, Chien-Chun Peng, Han-Yin Sun O7 Increased time outdoors prevents the onset of myopia: evidence from randomised clinical trials Ian G Morgan O8 Environmental risk factors and gene-environment interactions for myopia in the ALSPAC cohort Jeremy A. Guggenheim, Rupal L. Shah, Cathy Williams O9 Retinal metabolic profiling identifies declines in FP receptor-linked signaling as contributors to form-deprived myopic development in guinea pigs Jinglei Yang, Peter S. Reinach, Sen Zhang, Miaozhen Pan, Wenfeng Sun, Bo Liu, Xiangtian Zhou O10 The study of peripheral refraction in moderate and high myopes after one month of wearing orthokeratology lens Jun Jiang, Haoran Wu, Fan Lu O11 Axial length of school children around the earth's equatorial area and factors affecting the axial length Kazuo Tsubota, Hiroko Ozawa, Hidemasa Torii, Shigemasa Takamizawa, Toshihide Kurihara, Kazuno Negishi O12 Processing of defocus in the chicken retina by retinal ganglion cells Klaus Graef, Daniel Rathbun, Frank Schaeffel O13 Blue SAD light protects against form deprivation myopia in chickens, by local signaling within the retina Ladan Ghodsi, William K. Stell O14 Contributions of ON and OFF pathways to emmetropization and form deprivation myopia in mice Machelle T. Pardue, Ranjay Chakraborty, Han na Park, Curran S. Sidhu, P. Michael Iuvone O15 Response of the human choroid to defocus Michael J Collins O16 What can RNA sequencing tell us about myopic sclera? Nethrajeith Srinvasalu, Sally A McFadden, Paul N Baird O17 Overview of dopamine, retinal function, and myopia P. Michael Iuvone O18 The eye as a "robust" optical system and myopia Pablo Artal O19 Effect of discontinuation of orthokeratology lens wear on axial elongation in children Pauline Cho, SW Cheung O20 Myopia prevention in Taiwan Pei-Chang Wu O21 Alternatives to ultraviolet light and riboflavin for in vivo crosslinking of scleral collagen Quan V. Hoang, Sally A. McFadden O22 Absence of intrinsically photosensitive retinal ganglion cells (ipRGC) alters normal refractive development in mice Ranjay Chakraborty, Duk C. Lee, Erica G. Landis, Michael A. Bergen, Curran Sidhu, Samer Hattar, P. Michael Iuvone, Richard A. Stone, Machelle T. Pardue O23 Scleral micro-RNAs in myopia development and their potential as therapeutic targets Ravi Metlapally O24 Effects of the long-wavelength filtered continuous spectrum on emmetropization in juvenile guinea pigs Ruiqin Li, Qinglin Xu, Hong Zhon, Chenglin Pan, Weizhon Lan, Xiaoning Li, Ling Chen, Zhikuan Yang O25 Ocular and environmental factors associated with eye growth in childhood Scott A. Read O26 Overview- prevention and prediction of myopia and pathologic myopia Seang-Mei Saw O27 New insights into the roles of retinal dopamine in form-deprivation myopia and refractive development in C57BL/6 mice Shi-Jun Weng, Xiao-Hua Wu, Kang-Wei Qian, Yun-Yun Li, Guo-Zhong Xu, Furong Huang, Xiangtian Zhou, Jia Qu, Xiong-Li Yang, Yong-Mei Zhong O28 The effects of the adenosine antagonist, 7-methylxanthine, on refractive development in rhesus monkeys Earl L Smith III, Baskar Arumugam, Li-Fang Hung, Lisa A. Ostrin, Klaus Trier, Monica Jong, Brien A. Holden O29 Application of SWATH™ based next generation proteomics (NGP) in studying eye growth: opportunities and challenges Thomas Chuen Lam, Bing Zuo, Samantha Shan, Sally A. McFadden, Dennis Yan-yin Tse, Jingfang Bian, King-Kit Li, Quan Liu, Chi-ho To O30 How could emmetropization make use of longitudinal chromatic aberration? Timothy J. Gawne, John T. Siegwart Jr., Alexander H. Ward, Thomas T. Norton O31 Balance effect of dopamine D1 and D2 receptor subtype activation on refraction development Xiangtian Zhou O32 BMP gene expression changes in chick rpe in response to visual manipulations Yan Zhang, Yue Liu, Carol Ho, Eileen Phan, Abraham Hang, Emily Eng, Christine Wildsoet